Inscrições contemporâneas: a palavra-imagem no projeto da visualidade pós-moderna - Pires, Julie de Araujo (2010)
This thesis' purpose is the study of the potenciality of the written word and of the criative dynamic which give them form, studied in the dialog with works from contemporary visual arts. This research, taken under a trans-historical view, based on Hubert Damisch' theory, by which every work of art must be seen as an act and thought of the artist which reveals itself to the viewer in his dialog with them. This thesis' outlook is confirmed by Thierry de Duve's theoretical appropriation for whom a work is a reflection, leading to a critical approach, in which all aesthetic, critical and historical statement must be thought of as an conversation with the art work. From a contemporary art's perspective, this study concentrated in the posthistorical period, according to Arthur Danto's ldea of the end of the master narratives of art, and intended to question the formal possibilities of the word, related to the art work, and its role as an element of rupture and transformation of the modern art's limits. In this sense the written word turned into écriture, understanding this expression through Jacques Derrida's concepts, viewed in this thesis through the inscriptions in some works of Mira Schendel (1919-1988), Robert Smithson (1938-1973) and Rosâgela Rennó (1962), in paintings, drawings, engravings, art installations and photographies.